El arbitraje del Mar de China meridional: jurisdicción e implicancias - Giménez Losano, María Azul (2021)
The South China Sea is not exempt from legal storms. China claims historical rights over its islands and other marine features, while the Philippines counters that the claim is incompatible with the UNCLOS. This dispute led to the "South China Sea Arbitration", initiated by the Philippines under Annex VII of the UNCLOS. However, China refused to appear before the arbitral tribunal, arguing that it lacked jurisdiction to rule on the subject. The present research aims to address the jurisdictional issues arising from the award in the South China Sea dispute. Due to the complexities of the dispute, this essay seeks to analyze the jurisdiction of the arbitral tribunal constituted for the quarrel and, therefore, the effects of the award on China. For that purpose, this essay explores the applicable legal framework of the UNCLOS and the Permanent Court of Arbitration to analyze the claims of the Philippines, the possible limitations to the tribunal's jurisdiction and the impact of China's non-appearance on the proceedings. This storm triggered important legal and geopolitical questions, reflecting how the jurisdictional analysis varies in recent dispute settlement decisions. It will therefore be concluded that the arbitral tribunal for the "South China Sea Arbitration" was competent